Anti-Inflammatory and Immunomodulatory Mechanism of Tanshinone IIA for Atherosclerosis. (1st December 2014) - Chen, Zhuo; Xu, Hao
Abstract : Tanshinone IIA (Tan II A) is widely used in the treatment of cardiovascular diseases as an active component of Salvia miltiorrhiza Bunge. It has been demonstrated to have pleiotropic effects for atherosclerosis. From the anti-inflammatory and immunomodulatory mechanism perspective, this paper reviewed major progresses of Tan IIA in antiatherosclerosis research, including immune cells, antigens, cytokines, and cell signaling pathways.